2007
DOI: 10.1021/jm0708984
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonate Derivatives of Naphtho[2,3-b]thiophen-4(9H)-one and 9(10H)-Anthracenone as Highly Active Antimicrotubule Agents. Synthesis, Antiproliferative Activity, and Inhibition of Tubulin Polymerization

Abstract: Benzenesulfonate derivatives of naphtho[2,3-b]thiophen-4(9H)-one and 9(10H)-anthracenone were prepared and found to inhibit microtubule formation by an in vitro tubulin polymerization assay. Several analogues showed potent cytotoxic activity in an assay based on K562 leukemia cells with IC50 values of <100 nM. The methylamino analogue 14i was the most active compound in this assay (14i, IC50 K562: 0.05 muM). Antiproliferative activities of selected compounds were additionally evaluated against a panel of 12 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…[2] In polymer‐form, sulfone derivatives have gained prominence in material science, being used as the basis for proton exchange membranes due to their excellent chemical and thermal stability. [3] Sulfonate derivatives, or so‐called sulfonic esters, include bioactive compounds[4, 5] and are used as DNA alkylating agents to induce mutagenesis in experiments. [6] As the RSO 2 O − moiety is a good leaving group, sulfonate derivatives are commonly used as reagents in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In polymer‐form, sulfone derivatives have gained prominence in material science, being used as the basis for proton exchange membranes due to their excellent chemical and thermal stability. [3] Sulfonate derivatives, or so‐called sulfonic esters, include bioactive compounds[4, 5] and are used as DNA alkylating agents to induce mutagenesis in experiments. [6] As the RSO 2 O − moiety is a good leaving group, sulfonate derivatives are commonly used as reagents in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Amino substituent introduced to position 6 of naphthalimide was difficult to be acetylated (30) and might involve arrest of cell cycle (31). Different types of linkers, ethanolamine and sulfanilamide (32,33), connected naphthalimide with substituted benzoic acid to investigate their effects on biological activity. As shown in Figure 3, the target compounds 12a – e and 13a – d were prepared.…”
mentioning
confidence: 99%
“…General antimicrotubule agents, such as colchicine, podophyllotoxin, combretastatin, and phenstatin analogues, which recognize the same binding site on β-tubulin as is recognized by (−)-PLH (5), are structurally characterized as having multiple methoxy groups that make marked contributions to their potent antimicrotubule activities [31][32][33][34] ; however, multiple methoxy substitutions of a plinabulin derivative (e.g., compounds 24, 25, 38i, j) displayed low potencies. These results suggested that plinabulin and its derivatives recognized tubulin in a manner that differed from the binding by colchicine and its biological homologues.…”
Section: Modification Of the Benzophenone Moietymentioning
confidence: 99%